Branching Ratio Measurement in 23Ne Beta Decay - Rahangdale, H.; Mishnayot, Y.; Ohayon, B.; Hirsh, T.; Vaintraub, S.; Glick-Magid, A.; Gazit, D.; Ron, G. (HNPS Advances in Nuclear Physics, 2019)
We describe the branching ratio measurement experiment performed at Soreq Applied Research Accelerator Facility (SARAF) using the deuteron beam. We successfully produced 107/s 23Ne atoms in the run and used them to measure the branching ratio in 23Ne beta decay to the first excited state of 23Na. We provide some preliminary results of the experiment whose data analysis currently ongoing.